SOAP revisited - Queiroz, Maria João (2009)
The medical record is an essential tool for clinic management. Its contributions are invaluable: as an informational support, as a communication tool, as a medical care evaluator and as a research and traineeship contributor. In General Practice it is critical to create an organized and sustainable data storage for medical care. That need brings to discussion the relevance of using the old fashioned methods, especially SOAP, and its adaptability towards the new record applications. This article highlights SOAP strengths and flaws, suggesting some strategies to overturn them.